2014
DOI: 10.1101/gad.242644.114
|View full text |Cite
|
Sign up to set email alerts
|

PKR is activated by cellular dsRNAs during mitosis and acts as a mitotic regulator

Abstract: dsRNA-dependent protein kinase R (PKR) is a ubiquitously expressed enzyme well known for its roles in immune response. Upon binding to viral dsRNA, PKR undergoes autophosphorylation, and the phosphorylated PKR (pPKR) regulates translation and multiple signaling pathways in infected cells. Here, we found that PKR is activated in uninfected cells, specifically during mitosis, by binding to dsRNAs formed by inverted Alu repeats (IRAlus). While PKR and IRAlu-containing RNAs are segregated in the cytosol and nucleu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
128
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(137 citation statements)
references
References 62 publications
8
128
1
Order By: Relevance
“…2A); at present, it is entirely unclear how this might occur. A recent study showed that PKR is activated by inverted Alu repeats when these factors mix as the nuclear envelope breaks down during mitosis (29). PA has been shown to induce mitosis (30), and we considered whether mitosis could trigger a snoRNA-PKR interaction.…”
Section: Discussionmentioning
confidence: 99%
“…2A); at present, it is entirely unclear how this might occur. A recent study showed that PKR is activated by inverted Alu repeats when these factors mix as the nuclear envelope breaks down during mitosis (29). PA has been shown to induce mitosis (30), and we considered whether mitosis could trigger a snoRNA-PKR interaction.…”
Section: Discussionmentioning
confidence: 99%
“…One or both of these mechanisms could act upon mRNAs with EERs in their 3 ′ UTRs. In fact, PKR is activated by certain cellular dsRNAs only during mitosis, when the nuclear envelope is not present (Kim et al 2014), suggesting the presence of dsRNA in the cytoplasm might be dependent on cell cycle.…”
Section: Comparison Of Eer Data Sets With Data Sets Of Related Studiesmentioning
confidence: 99%
“…Recent studies reveal that cellular dsRNAs are capable of activating innate immune signaling pathways under various conditions (Nakamura et al 2010;Kim et al 2014). We were curious whether the expression of EERs could be regulated under conditions of stress, for example, during infection.…”
Section: Subsets Of Eers Are Differentially Expressed During Stress Amentioning
confidence: 99%
See 1 more Smart Citation
“…′ UTR IRAlus have the potential to bind and activate another dsRNA-binding protein, the translational inhibitor protein kinase R (PKR), making 3 ′ UTR IRAlus negative regulators of mRNA translation both in cis and in trans (Elbarbary et al 2013;Kim et al 2014). STAU1 also competes with PKR for binding to 3 ′ UTR IRAlus so as to alleviate translational repression (Elbarbary et al 2013).…”
mentioning
confidence: 99%